2018
DOI: 10.1038/s41467-018-05763-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IRE1 RNase activity modulates the tumor cell secretome and enhances response to chemotherapy

Abstract: Triple-negative breast cancer (TNBC) lacks targeted therapies and has a worse prognosis than other breast cancer subtypes, underscoring an urgent need for new therapeutic targets and strategies. IRE1 is an endoplasmic reticulum (ER) stress sensor, whose activation is predominantly linked to the resolution of ER stress and, in the case of severe stress, to cell death. Here we demonstrate that constitutive IRE1 RNase activity contributes to basal production of pro-tumorigenic factors IL-6, IL-8, CXCL1, GM-CSF, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
191
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 225 publications
(204 citation statements)
references
References 44 publications
8
191
0
5
Order By: Relevance
“…Knockdown of IRE1 expression in a panel of colon cancer cell lines reduced cell proliferation in vitro and in vivo [Li et al., ]. Similarly, inhibiting IRE1 RNase activity reduced the proliferation of breast cancer cells in vitro [Logue et al., ]. The observed reduction in proliferation was not associated with increased cell death but was linked in vitro to the arrest of cells in G1 [Li et al., , Logue et al., ], indicating IRE1 signalling can impact on cell cycle dynamics.…”
Section: The Upr In Tumour Initiation Development and Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of IRE1 expression in a panel of colon cancer cell lines reduced cell proliferation in vitro and in vivo [Li et al., ]. Similarly, inhibiting IRE1 RNase activity reduced the proliferation of breast cancer cells in vitro [Logue et al., ]. The observed reduction in proliferation was not associated with increased cell death but was linked in vitro to the arrest of cells in G1 [Li et al., , Logue et al., ], indicating IRE1 signalling can impact on cell cycle dynamics.…”
Section: The Upr In Tumour Initiation Development and Progressionmentioning
confidence: 99%
“…Similarly, inhibiting IRE1 RNase activity reduced the proliferation of breast cancer cells in vitro [Logue et al., ]. The observed reduction in proliferation was not associated with increased cell death but was linked in vitro to the arrest of cells in G1 [Li et al., , Logue et al., ], indicating IRE1 signalling can impact on cell cycle dynamics. The Cyclin D1:CDK4 complex promotes movement through the G1 phase of the cell cycle by inhibiting retinoblastoma protein.…”
Section: The Upr In Tumour Initiation Development and Progressionmentioning
confidence: 99%
“…However, these cells also exhibited increased adhesion and migration on Matrigel through activation of RhoA . In TNBC cell lines IRE1α RNase activity is required for expression of protumorigenic factors such as IL‐6, IL‐8, CXCL1, and TGF‐β, and contributes paclitaxel mediated expansion of tumor‐initiating cells …”
Section: Ire1α Outputs and Cancer: Riddmentioning
confidence: 99%
“…Given the importance of both XBP1 signaling and RIDD in tumor development, it can be surmised that small molecule inhibitors or activators of the IRE1α RNase domain have potential as a therapeutic strategy in combination with chemotherapy. For example, Logue et al showed that MKC8866, a small molecule IRE1α RNase inhibitor, strengthened the response to paclitaxel by downregulating the synthesis and secretion of protumorigenic cytokines in triple‐negative MDA‐MB‐231 breast cancer cells. In vitro mammosphere formation was notably reduced in these cells, suggesting that this reduction in the number of tumor‐initiating cells is a direct consequence of an IRE1α‐dependent decrease in protumorigenic cytokines .…”
Section: Inhibition and Activation Of Ire1α Signaling In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation